ANALISIS MUTASI T1631C DAN C1638T DI GENA X PADA PASIEN DENGAN HEPATITIS B KRONIS DAN PENYAKIT HATI TAHAP LANJUT DI RSUP DR. SARDJITO YOGYAKARTA - , SAGITA ADVENTIA; , dr. Didik Setyo Heriyanto, Ph.D, Sp.PA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Hepatitis B Virus (HBV) infection is a major public health problem. Approximately, more than 2 billion people are infected with HBV and there are 350 million chronic carriers around the world. Every year, more than half a million people are dead due to acute or chronic infection of HBV. Indonesia is categorized into a country with medium until high endemicity of HBV with carrier rate around 5â20% among population. Studies about viral factors, especially HBV mutation which contributed into the development of advanced liver diseases have been conducted. However, the results remain inconclusive. Thus, this research is focused on the identification of specific mutation in X gene of HBV which could be used as a predictive marker for advanced liver diseases. Objective: To know prevalence of X gene mutation T1631C and C1638 in patients with chronic HBV infection and advanced liver diseases in RSUP Dr. Sardjito Yogyakarta. Methods: Cross-sectional study involved 80 patients with positive HBsAg status in RSUP Dr. Sardjito Yogyakarta. Patients are divided into two groups, 40 patients with chronic HBV infection and 40 patients with advanced liver diseases. X gene mutation is analysed by nested PCR and direct sequencing. Results: X gene mutation in C1638T and T1631C were found in 19 (47,5%) and 18 (45%) of 40 advanced liver diseases patients, respectively. In the group of patients with chronic HBV infection, mutation in C1638T and T1631C were only found in 2 (5%) and 2 (5%) of 40 patients, recpectively. This difference is statistically significant. Conclusion: X gene mutation in C1638T and T1631C are more prevalent in group of patients with advanced liver diseases compared with group of patients with chronic HBV infection. Therefore, X gene mutation could be used as predictive marker for advanced liver diseases development process.